Bureaucracy, instructions, and paperwork – The gathering of data about the three kingdoms of nature in the americas, 1770-1815 - Podgorny, Irina (2019)
Over the past thirty years, Spanish and Mexican historians of science have reversed the idea that the Spanish metropolis had abandoned its former territories to a state of darkness in terms of science, an understanding spread during the Revolution and Independence and adopted by late nineteenth-century historiography. Current research revealed instead the complex dynamics of the expeditions sponsored by the Crown and the enormous quantity of materials about “the three kingdoms of nature” collected during the last third of the eighteenth century in the Royal Cabinet, the Royal Pharmacy of Madrid and in the major cities of the viceroyalties. An analysis of the products from the Indies in medicine, commerce, and mining as well as the envoy of experts to the area reveals a history of knowledge as long and complex as that of the Dutch or British.